Anglican Liturgy as a Model for the Italian Church? The Italian Translation of the Book of Common Prayer by George Frederick Nott in 1831 and its Re-edition in 1850 - Stefano Villani (Revue Française de Civilisation Britannique)
The first manuscript Italian translation of the Book of Common Prayer was made in 1608 by  the chaplain to James I’s ambassador in Venice with the help of Paolo Sarpi. This translation was part of an English propaganda plan to instigate a schism in the Church of Venice. A completely different translation was printed in London in 1685, for propaganda reasons, as a sort of poisoned gift to the Catholic King, James II. A significant number of Italian translations of the Book of Common Prayer were made in the 18th and 19th centuries. They served purposes that often had nothing to do with worship, including providing a convenient way for English people to learn Italian. In 1831 George Frederick Nott prepared a new translation of the Book of Common Prayer, which was published in Livorno, though with false attribution to London. The Society for Promoting Christian Knowledge (SPCK) used this Italian version to promote the Church of England as a possible model for a reformation of the Roman Catholic Church. In the 19th century, a number of Anglicans vainly engaged in attempts to convince the Waldensian Church to become the instrument of the conversion of Italy to Protestantism thanks to its adoption of episcopacy and the Book of Common Prayer.